An online non-meditative mindfulness intervention for people with ALS and their caregivers: a randomized controlled trial. Issue 1 (2nd January 2022) - Pagnini, Francesco; Phillips, Deborah; Haulman, Anne; Bankert, Matthew; Simmons, Zachary; Langer, Ellen
Abstract: Objectives : Mindfulness-based interventions seem to be effective in promoting QOL of ALS patients and caregivers, but most require substantial time. In the Langerian approach, mindfulness can be easily promoted with mental tasks and short lectures. This study aims to explore the impact of an ALS-specific online Langerian mindfulness training program on QOL of ALS patients. Methods: We developed and tested with an Randomized Controlled Trial (RCT) a 5-week active learning mindfulness program. Participants were recruited from the ALS clinic at Penn State Health and online and were randomly assigned to either the mindfulness group or a wait-list control group. The primary outcome was the patient's QOL after the treatment. 3 and 6-month follow-ups, together with anxiety, depression, care burden, and physical function, assessed at all times for both patients and caregivers, were explored as secondary outcomes. Results: 47 ALS patients and 27 caregivers were recruited. Among the ALS patients, the experimental group reported higher levels of QOL at the end of the treatment (d = 0.54). Moreover, they showed lower values of depression, anxiety, and negative emotions, compared to the controls, over time. The caregivers from the mindfulness group reported lower scores of care burden, depression, and anxiety, with higher values of energy and emotional well-being over time. Conclusions: This small RCT provides preliminary evidence that this intervention leads to an increase of QOL and a reduction in psychological comorbidities in ALS patients and caregivers. Given the relatively short time commitment, it may be easily implemented by the ALS community.